A Clinical Study on Syndrome Differentiation of Male with Teeth-Mark Tongue - Soo-Jung Lee; Sang-In Baek; Byung-Gwon Lee; Ah-Ram Lee; Koang-Lok Kim; Hyun-Min Yoon; Won-Il Kim (Korean Pharmacopuncture Institute, 2010)
Objectives : The purpose of this study was to analyze the propensity and find out the Syndrome Differentiation of teeth-mark tongue by taking survey and body examinations with 178 male patients. 164 patients out of 178 were checked up on Heart Rate Variability (HRV), Accelerated Photoplethysmograpy (APG), Body Composition. This study was also planned to find out the distinctive characteristics of teeth-mark tongue diagnosis and compare differences between Qi-Deficiency and Accumulation of Dampness and Phlegm patients group. Methods : The questionnaire was carried out targeting 178 male with teeth-mark tongue respondents among who had Oriental Health Examination and patients from the 3rd oriental-internal medicine department in Dongeui Hospital from 1st , March 2005 to 30th, April 2010. Only 164 patients were checked on HRV, APG and Body composition examinations. Results : It showed that 86 patients had Qi-Deficiency and 78 had Dampness and Phlegm but 14 couldn't be categorized. The major symptoms of Qi-Deficiency compared to Dampness and Phlegm were 'Frequent running nose', 'Soft stool', 'Chronic fatigue', and 'Eyestrain'. On the contrary, Dampness and Phlegm's dominant symptoms were 'Chest discomfort', 'Feeling bloated', 'Back pain', 'Feeling sluggish', and 'Itchy skin'. However, all symptoms were not matched with the Syndrome Differentiation of Qi-Deficiency or Dampness and Phlegm. It also showed that teeth-mark tongue patients' frequent symptoms were 'Stuffy nose', 'Feeling bloated', 'Oliguria', 'Shoulder pain', 'Chronic fatigue', 'Eyestrain' and these symptoms were matched with the Syndrome Differentiation of Qi-Deficiency and Dampness and Phlegm. In the results from this study, there were no significant differences between Qi-Deficiency and Dampness and Phlegm. Conclusions : It is hard to conclude that teeth-mark tongue could be only one to diagnose Qi-Deficiency or Dampness and Phlegm with 3 examinations.